2020
DOI: 10.3390/catal10121410
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Dried Ni Catalysts with Tailored Properties for CO2 Methanation

Abstract: A catalyst production method that enables the independent tailoring of the structural properties of the catalyst, such as pore size, metal particle size, metal loading or surface area, allows to increase the efficiency of a catalytic process. Such tailoring can help to make the valorization of CO2 into synthetic fuels on Ni catalysts competitive to conventional fossil fuel production. In this work, a new spray-drying method was used to produce Ni catalysts supported on SiO2 and Al2O3 nanoparticles with tunable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 74 publications
(145 reference statements)
0
23
0
Order By: Relevance
“…CO 2 methanation experiments were conducted with a 20 wt% Ni/SiO 2 catalyst produced with a spray-drying method as described in the work of Kreitz et al 74 A solution of colloidal SiO 2 nanoparticles with a primary particle size of 8 nm and Ni(NO 3 ) 2 was sprayed into a tubular furnace operated at 673 K using an atomizer to initiate a one-step calcination and assembly of Ni/SiO 2 nanoparticles. These nanoparticles were collected on a filter and heat-treated at 673 K for 3 h. The experiments were conducted with a Ni/SiO 2 catalyst because the acidic surface of the silica does not adsorb CO 2 8 and, therefore, does not participate in the methanation mechanism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 methanation experiments were conducted with a 20 wt% Ni/SiO 2 catalyst produced with a spray-drying method as described in the work of Kreitz et al 74 A solution of colloidal SiO 2 nanoparticles with a primary particle size of 8 nm and Ni(NO 3 ) 2 was sprayed into a tubular furnace operated at 673 K using an atomizer to initiate a one-step calcination and assembly of Ni/SiO 2 nanoparticles. These nanoparticles were collected on a filter and heat-treated at 673 K for 3 h. The experiments were conducted with a Ni/SiO 2 catalyst because the acidic surface of the silica does not adsorb CO 2 8 and, therefore, does not participate in the methanation mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Ar was employed as an internal standard and to reduce thermal effects. A temperature-scanning experiment as described in Kreitz et al 74 was used to investigate the methanation reaction over the entire temperature range up to 773 K. During the temperature scan, the temperature was linearly raised with a rate of 20 K min –1 (see Table S3 for a summary). The product mole fraction was analyzed with a high temporal resolution using a mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…to thermodynamic equilibrium that is reached in the experiment at temperatures beyond 700 K. An activation energy of 84 kJ mol −1 was determined, which is comparable to other Ni/SiO 2 catalysts. 10,64,87,88 Results from the microkinetic model generated by RMG with the reference settings shows a significantly lower activity at lower temperatures. CH 4 formation starts at 600 K and reaches the maximum rate at 700 K. The production of CO starts at a temperature of 650 K and directly reaches the equilibrium concentration.…”
Section: Resultsmentioning
confidence: 98%
“…This assumption is justified since no deviation between steady-state and transient results was observed in the experiments. 64 The parameters for the simulation are summarized in Table S3. As a simplification, no lateral interactions among the adsorbates were considered in the surface mechanism.…”
Section: Microkinetic Modelingmentioning
confidence: 99%
“…It focused mainly on the dielectric barrier discharge (DBD) method used both in the process of initial catalyst formation and its final activation. It was found that such a procedure improved the catalytic properties and provided better anti-carbon deposit performance compared to the catalyst made only by thermal treatment [34][35][36][37][38]. It should be noted, however, that this is only a plasma treatment of "classically" produced catalysts.…”
Section: Introductionmentioning
confidence: 99%